Distributional impacts of global food price shocks in South Africa: Case of Russia-Ukraine conflict - Faaiqa Hartley; Sherwin Gabriel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
The world has faced an increasing number of global shocks that have resulted in large and unpredictable changes in global prices, particularly of food. These increases, coupled with the negative impacts of shocks to economic growth, have had damaging effects on welfare, hunger, and diets. Future global price shocks are likely, whether spurred by geopolitical tensions, climatic extremes, or natural disasters. This paper assesses the distributional impact of food price shocks on households in South Africa using price increases during the 2022 Russia-Ukraine war as a case study. To assess the economy-wide effects on households, a computable general equilibrium model for South Africa is used. Outputs from the model are linked to an accounting-based microsimulation to assess the impacts on poverty and inequality. Government measures to alleviate price pressures are also assessed and compared to alternative possible interventions to ascertain the benefits and trade-offs of different policy responses.
Keywords: C68; E62; F41; O5; 330; computable general equilibrium; global shocks; microsimulation; policy response; poverty